Dampak Cyberbullying terhadap Kesehatan Mental Remaja di Era Digital : Studi Literatur - Brigita Divaria Pakpahan; Nayla Rahma Dwi Novita; Fatma Tresno Ingtyas; Laurena Ginting (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
Cyberbullying is a form of online violence that is increasingly widespread in the digital era, with serious impacts on adolescent mental health, such as depression, stress, and anxiety. This study aims to examine the impact of cyberbullying on adolescent mental health through a literature review covering 10 accredited journals indexed by SINTA, Google Scholar, and DOAJ. The method used is a literature review with a comparative analysis approach to previous research findings. The results of the study indicate that victims of cyberbullying often experience decreased self-esteem, emotional disturbances such as shame and fear, and decreased motivation to learn. These disturbances can then increase the risk of depression among adolescents. Decreased self-esteem and increased anxiety also impact their academic performance and social engagement. Based on these findings, it can be concluded that cyberbullying is a significant factor threatening adolescent mental health. Therefore, serious attention is needed from various parties, including schools, families, and communities, to provide protection and psychosocial support to victims. Recommended interventions include digital literacy education, family support, and counseling programs that can help adolescents overcome the negative impacts of cyberbullying and prevent lasting effects on their mental health.